The Effect of Commercial Ration with Green Bean Sprout Peels Flour To Performance of Male Bali Duck Aged 0-8 Weeks - K. Y. P., Laksamana; Siti, N W.; Puspani, E. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
This study aimed to determine the effect of commercial ration with green bean sprout peels flour on performance of male bali duck. Research use completely randomized design (CRD) with three treatments, each treatment using five replications and each replication using three male bali duck. The treatments it gives is ; P0 (commercial ration of 100%), P1 (replacement of 6% commercial ration with bean sprout peels flour) and P2 (replacement of 12% of commercial ration with bean sprout peels flour). The variables were observed in this study is the initial weight, consumption of rations, drinking water consumption, final body weights, increase of body weight and Feed Conversion Ratio. The results showed that the replacement of 6% and 12% commercial ration with green bean sprout peels flour effect is not significant (P>0.05) to consumption of rations, drinking water consumption, final body weights, increase of body weight and Feed Conversion Ratio. Based on the results of this study concluded the replacement of 6% and 12% commercial ration with green bean sprout peels flour giving effect same good with commercial rations to performance of male bali duck aged 0-8 weeks.   Keywords : Male bali ducks,  green bean sprout peels flour, performance, commercial ration